1989
DOI: 10.3109/00016358909004805
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of three techniques for measuring wear of dental restorations

Abstract: Measurements of impression profiles, profilometer registrations, and scanning electron microscopy (SEM) photogrammetry of metal dies simulating worn restorations were compared as possible techniques for measuring and recording the wear rate of tooth restorations. The results showed that measurements of impression profiles and SEM photogrammetry gave the most accurate results adjacent to regions simulating steep cavity margins, whereas the profilometric technique gave erroneous results in these regions. These e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 8 publications
0
8
0
1
Order By: Relevance
“…secondary dentin formation, attrition, color change of teeth, etc. [13][14][15][16][17][18][19][20][21][22][23]. Methods of age estimation using tooth wear and the development of permanent teeth were reported in 2000, 2007 and 2008 by our lab, and have been proved to be valuable and useful in the field [24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…secondary dentin formation, attrition, color change of teeth, etc. [13][14][15][16][17][18][19][20][21][22][23]. Methods of age estimation using tooth wear and the development of permanent teeth were reported in 2000, 2007 and 2008 by our lab, and have been proved to be valuable and useful in the field [24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…Profilometry by the use of a stylus was applied in several studies, and showed more errors compared to Scanning electron microscopy (SEM), probably due the morphology of the stylus. SEM on the other hand had its disadvantages by the need of complex software, and a low precision of hardware components 34 .…”
Section: Recording Of Tooth Wearmentioning
confidence: 99%
“…Two, however, contained incomplete data 26,28 . The missing data were sourced from previously published work, allowing analysis to be completed 33,34 .…”
Section: Search Inclusion and Exclusionmentioning
confidence: 99%
“…3590 O perfilômetro é um instrumento utilizado para medir o perfil de diferentes superfícies, com o objetivo de quantificar a rugosidade dessas. Esta técni-ca tem sido vastamente utilizada em odontologia, principalmente no campo da dentística restauradora, para avaliar a rugosidade de materiais restauradores e da dentina [12][13][14] . Contudo, não se encontram relatos na literatura utilizando a técnica proposta nesta investigação para análise de materiais obturadores endodônticos.…”
Section: Introductionunclassified